Deuterium trapping in tungsten irradiated with deuterium plasma at high temperatures - Rakhadilov, B.K.; Skakov, М.K.; Miniazov, A.Zh.; Zhurerova, L.G.; Nugumanova, A.B.; Khassenov, A.K.; Karabekova, D.Zh. (of the E.A. Buketov KarU publ., 2020)
This work was attended to the study of the accumulation of deuterium, also to the investigation of the process of capture of deuterium in tungsten samples upon irradiation with a plasma beam. It was shown that after irradiation on the surface, a change in the surface is observed as the development of the relief as a result of nonuniform etching of the surface. The degree of change in the relief and structure of the surface layer of the irradiated samples depends on the irradiation temperature. The accumulation of deuterium tungsten under irradiation with deuterium plasma was studied. The conducted thermal desorption analysis of tungsten samples irradiated with deuterium plasma showed that the tungsten surface is saturated with deuterium. The data obtained by the method of emission spectrometry and thermal desorption spectrometry showed that the majority of the captured deuterium accumulates at a depth under the 7 μm.
Keywords: deuterium; irradiation; tungsten; a plasma beam